THE INFLUENCE OF SPIRITUAL HERITAGE AND UNIVERSAL VALUES ON THE DEVELOPMENT OF YOUTH PROFESSIONAL CULTURE (Western European Journal of Historical Events and Social Science, 2025)
This study examines the impact of spiritual heritage and universal values on the formation and development of professional culture among young people. It highlights how ethical principles, moral traditions, and cultural heritage shape the professional behavior, work ethics, and interpersonal skills of youth in modern society. The research emphasizes the importance of integrating spiritual and moral values into educational and professional environments to foster well-rounded, socially responsible, and culturally aware professionals.